Experimental Marketing Untuk Menentukan Kombinasi Terbaik Dalam Promosi Penjualan Dengan Metode Desain Faktorial 2k (Studi Kasus : Thriftshop Sadean) - Muhammad, Katon; Putri, Raisani Dianis; Krisnawati, Maria (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2024)
Social media is not only used as a way for communication, but it can also be used by businesses for marketing. Sadean.ofc is a second-hand goods business that offers branded used clothing that utilizes Instagram and Tiktok social media to help their promotional activities. The purpose of this study is to find the optimal combination of promotional and analyze how social media affects sales at Sadean.ofc. The method used in this study was a 2K factorial experimental design and Duncan's test. Promotional activities were conducted in this experiment with two factor levels, high costs and low costs, and three replications. The experimental results show the main effect A has an impact with Fcount (5.35) > Ftable (5.31) and main effect A with Fcount (5.98) > Ftable (5.31) so that H0 is rejected. Based on the percentage value of the contribution factor B, which has a contribution percentage of 25.24%, factor A is 22.17%. Thus, it can be concluded that the main effect B makes the greatest contribution to sales of Sadean.ofc products. In Duncan's test, it was found that there was a significant difference in the A1B1 and A2B2 treatments.